Synthesis, Properties and Spatial Structure of 4-[(3,5-Dimethyl-1,2-oxazol-4-yl)sulfonyl]cytisine - Ibrayev, M.K.; Nurkenov, O.A.; Rakhimberlinova, Zh.B.; Takibayeva, A.T.; Turdybekov, D.M.; Seilkhanov, T.M.; Issabayeva, M.B.; Kelmyalene, A.A.; Kezdikbayeva, A.T.; Mendibayeva, A.Z. (Plants, 2023)
This article has studied the synthesis of a new derivative of the known alkaloid cytisine contained in the seeds of plants of Cytisus laburnum L. and Thermopsis lanceolata R.Br., both of the Lugiminosae family. The new compound has been obtained from two biologically active compounds, such as isoxazole and cytisine. It has been demonstrated that the reaction led to the single-stage method under very mild conditions to obtain 4-[(3,5-dimethyl-1,2-oxazol-4-yl)sulfonyl]cytisine. This class of compounds is promising for obtaining the new biologically active compounds. This article has examined, in detail, a structure with using the 1H and 13C NMR and two-dimensional NMR spectroscopy of COSY (1H-1H), HMQC (1H-13C) and HMBC (1H-13C). As a result, the homo- and heteronuclear spin-spin couplings should be established. The X-ray diffraction analysis has determined the spatial structure of a new derivative based on the cytisine alkaloid. Thus, its hemorheological activity has been studied.
Keywords: sulfo-derivatives of azoles; alkaloid cytisine; spatial structure; hemorheological activity; 1H; 13C; 2D NMR spectroscopy; X-ray diffraction analysis